Avaliação psicométrica da prova de títulos de especialista em cardiologia da Sociedade Brasileira de Cardiologia - Marinho, Gustavo Eugênio Martins (2021)
Introduction: Professional certification is increasingly present in the medical curriculum, ei-ther due to market demands or due to legal demands. After a long initial journey to training, doctors can choose between two paths to obtain the title of specialist, a residency program or a medical specialization, provided they are certified by official entities. In the latter, upon completing the specialization, the doctor must perform a test to obtain the title of specialist. The Brazilian Society of Cardiology, with the assistance of the Judging Panel on Cardiology Specialist Titles, promotes annually a test for this purpose. Regarding the elaboration of items, until the present study, there had been no psychometric evaluation of the test for the Title of Specialist in Cardiology (TSC), considering the Classical Test Theory (CTT) and the Item Re-sponse Theory (IRT). These theories seek, in a technical way, to evaluate the quality of the items involved in a test and, statistically, yield a profile of the test regarding the degree of difficulty, power of discrimination, and possibility of scoring due to guessing, which allows us to critically analyze the quality of the test performed. Objectives: To evaluate the psycho-metric properties of the TEC test in 2019, considering the CTT and IRT parameters. Materials and methods: Observational study, with the psychometric analysis of the 120 questions of the test performed by 1,120 (one thousand and one hundred and twenty) candidates to obtain the Title of Specialist in Cardiology, in the year 2019. Results: The analysis using CTT demonstrated that the test presents a good distribution of the items regarding the degree of difficulty, with a tendency towards ease. Through the IRT, it was possible to verify that, of the 118 questions evaluated, only 49 (41.5%) have a satisfactory discrimination parameter. Conclusion: The results of this study present an unprecedented view of the TEC test and, for the official entities that organize the test, they may trigger a series of discussions and pro-posals for the future elaboration of tests in the scope of Cardiology and other medical special-ties